Structural and elastic properties, Vickers hardness and Debye temperature of (B1) BP: DFT study - Daoud, Salah (International Journal of Physical Research, 2020)
A theoretical study of the structural parameters and elastic constants of boron phosphide (BP) compound with cubic rocksalt structure has been carried out using ab-initio density functional theory (DFT) and density functional perturbation theory (DFPT) calculations based on the plane-wave and pseudopotential (PW-PP) approach. Elastic anisotropy factors, Cauchy pressure, inverted Pugh’s ratio, aggregate mechanical moduli (shear modulus, Young's modulus and Poisson's ratio), Vickers hardness HV, elastic wave velocity as well as the Debye temperature θD and the melting point have been also calculated. Our obtained results are in general in good agreement with other data of the literature. The deviation between our obtained value (4.225 Å) of the lattice constant and the theoretical value (4.282 Å) of the literature is around 1.33%, while that between our obtained value (169.7 GPa) of the bulk modulus and the theoretical one (171 GPa) is only around 0.77%. The calculated values of HV and θD were found at around 30.5 GPa and 1254 K (1314.4 K), respectively.